PELATIHAN PEMBUATAN KERAJINAN TRADISIONAL DAUN PANDAN DAN TEKNIK PEWARNAANNYA KEPADA MAHASISWA PROGRAM STUDI BIOLOGI UNIVERSITAS CENDERAWASIH - Lisye Iriana Zebua; Ervina Indrayani (JURNAL PENGABDIAN PAPUA, 2018)
Pandan leaves is one of the commodities of non timber forest products that have potential and usefeul as raw materian of handicraft. According to market demand and over time, Pandanus crafts are made into a variety of creative and innovative forms, such as handbags, sandals, storage boxes, file boxes, and so on. Community service activity is aimed to train and guide the students in Biology Departmentto create innovative products from pandan leaf crafts and to train them to do pandan leaf cloring techniques so that it becomes a quality craft materials. The results of the devotion work well, the students managed to cerate some innovative products, including sandals, hand fans and placemates. Based on the questionnaire analysis shows that 100% of students get new knowledge about handicrafts and coloring techniques pandanleaf staining, and activities like this can be used as extracurricular activities for students in the department of Biology. Keywords: Pandan leaf, handycrafts, staining technique